2014
DOI: 10.1002/app.40880
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and local mechanical surface characterization of ballistic fibers via AFM

Abstract: As-received morphologies, defect structures, and contact moduli of Kevlar KM2 Plus and three other ballistic fibers varying in chemistry and processing, were observed and compared using atomic force microscopy (AFM) and instrumented nanoindentation (NI) techniques. Surface features and defects were defined and measured for each fiber chemistry: p-phenylene terephthalamides (PPTA including KM2 Plus and Twaron), co-polymer aramid (AuTx), and ultra high molecular weight polyethylene (UHMWPE including Dyneema). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The nanoscale fibrillar crystals which compose the fiber are often considered the fundamental building block of these fibers, but knowledge of their characteristic size and interconnectivity in high tenacity fibers is lacking. In addition, the appearance of epitaxial structures on the surface of highly drawn fibers has been noted [23,24] and a deeper understanding of their origin may provide valuable insight into the evolution of the interior structure of a fiber under common processing conditions. Through the comparison of high resolution microscopy techniques and wide angle X-ray diffraction, the research herein aims to quantify dimensions of fibrillar crystals and epitaxial features as well as provide some insight into the nano and mesoscale interactions between fibrils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoscale fibrillar crystals which compose the fiber are often considered the fundamental building block of these fibers, but knowledge of their characteristic size and interconnectivity in high tenacity fibers is lacking. In addition, the appearance of epitaxial structures on the surface of highly drawn fibers has been noted [23,24] and a deeper understanding of their origin may provide valuable insight into the evolution of the interior structure of a fiber under common processing conditions. Through the comparison of high resolution microscopy techniques and wide angle X-ray diffraction, the research herein aims to quantify dimensions of fibrillar crystals and epitaxial features as well as provide some insight into the nano and mesoscale interactions between fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…The type of high draw ratios and elevated temperature at which this occurs is key to the development of the extended chain morphologies from which the fiber derives high strength and stiffness. Other research has revealed the presence of these epitaxial structures on the surface of highly drawn fibers [23,24], raising the question of their origin and significance in the discussion of structure/property relationships. As these fibers are incorporated into composite materials, a key metric in determining their effectiveness in load bearing and impact resistance is their ability to absorb and dissipate energy.…”
Section: Introductionmentioning
confidence: 99%
“…9 The internal structure of AuTx consists mostly of large corrugated fibril bundles rather than single fibrils, with a typically cylindrical fiber shape. 28 At lower strains, the experimental results were consistent; at larger strains past approximately 40%, stress deviations become significantly larger (Figure 13). This may be attributed to the sudden failure and fibrillation of the fibers past the 40% strain mark, as described by Singletary et al 6 for PPTA fibers.…”
Section: Rusar -Autx Fibersmentioning
confidence: 70%
“…Nano-fibrils consist of stacks of crystallites separated by thin non-crystalline plates, portions of which are spanned by inter-crystalline bridges giving a shish-kebab structure 130 . Polyethylene ballistic fibers exhibit a shish-kebab crystalline structure reported through AFM characterization by Strawhecker and Cole 131 . It was mentioned earlier that post failure investigation of impacted fabrics showed deformation and failure modes including permanent transverse compressive deformation, fibrillation and transverse shear (cutting) failure.…”
Section: Ballistic Fibrilsmentioning
confidence: 84%
“…130 PE ballistic fibers exhibit a shish-kebab crystalline structure reported through AFM characterization by Strawhecker and Cole. 131…”
Section: Experiments On Fibrils Fibers Yarns and Fabricsmentioning
confidence: 99%